Methicillin-resistant Staphylococcus aureus among healthcare workers: screening, risk factors and treatment - Rahman, Rahmathulla Safiyul; Beyari, Badr Mohammed; Samarin, Kawlah Essam; Alamri, Khalid Mohammed; Bader, Marwan Abdulaziz; Alnemer, Rashed Abdullah; Baothman, Eman Abdulrahman; Bilal, Asaad Abdellahi; Alkahmous, Hadil Ali; Alshehri, Arwa Abdulhadi; Alsalamah, Mona Yousef (International Journal Of Community Medicine And Public Health, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is a common pathogen of clinical significance within the community and healthcare settings. It has been reported with a variety of infections, including endocarditis, bloodstream infections, pneumonia, joint and bone infections, and soft tissue and skin infections. Although many efforts have been exerted to eradicate the rates of infections and studies have reported a decreasing pattern in the prevalence rates over the years, it has been demonstrated that MRSA represents a significant challenge to the healthcare systems and the affected patients. In this literature review, we have provided a discussion regarding the risk factors, screening, and treatment of MRSA among healthcare workers (HCWs) based on the evidence obtained from the current relevant studies in the literature. HCWs are at increased risk of MRSA colonization, and many risk factors have been identified. These mainly include poor hygiene practices, chronic skin diseases, and having a history of working in an MRSA-endemic country. Decolonization practices are the main line of treatment of MRSA colonization among HCWs because antibiotic therapy is usually of limited use because of the increasing resistance to a wide range of antibiotics. Applying adequate interventions as taking care of hand hygiene and using alcohol-based disinfectants is recommended to achieve better outcomes. Increasing awareness among HCWs is also a potential approach to achieve better management.